The Use and Instruction of Language Learning Strategies : A Comparative Study of Ninth-Graders and Adult Learners of English and the Perceptions of Their Teachers - Fränti, Sirja (fi=Turun yliopisto|en=University of Turku|, 2018)
The purpose of the study was to examine the effects of age on language learning strategy use in learning English as a second language, comparing school-aged children and adult students. In addition, teacher perceptions of their students’ strategy use and their experiences of providing strategy instruction were investigated. The participants of the study were 327 Finnish ninth-graders and adults students of English and 26 teachers, representing different regions of the country. Both quantitative and qualitative methods were used for data collection and analysis. The frequency of the learners’ strategy use and their teachers’ perceptions of it were studied employing Oxford’s SILL questionnaire (1990), version 7.0 for ESL/EFL context. Teachers’ experiences of strategy instruction were examined with the help of written narratives. According to the results, adult students use different language learning strategies more frequently than ninth-graders do. Despite these statistically significant differences, the two learner groups still prefer using similar kinds of strategies. The most frequently employed strategies were metacognitive, compensation and cognitive strategies, whereas memory strategies were used the least frequently. Neither ninth-graders nor adult students seem to find the evaluation of their own strategy use particularly difficult. Teachers of both learner groups tend to overrate their students’ strategy use but are, at the same time, quite well aware of the types of strategies their students prefer using. Nevertheless, the evaluation of students’ strategy use is considered difficult. With regard to teachers’ experiences of teaching the strategies, teachers of ninth-graders and adult students seem to value the importance of language learning strategy use and instruction. However, their perceptions of both the strategies and the instruction of them are mainly based on the teachers’ personal experiences as language learners or on the strategy instruction they have received themselves, not on research or theoretical data. The findings of the study imply that although age as an individual factor may affect the frequency of learners’ strategy use, learners still prefer using similar kinds of strategies. The results also indicate that teachers may be better aware of their students’ strategy use than what earlier studies have suggested. On the other hand, due to the difficulty of evaluating students’ strategy use and the teachers’ lack of theoretical knowledge, there is need for more systematic training for teachers of English in how to identify and teach learning strategies. This will help them to guide their students in becoming more self-regulated language learners who effectively utilise different kinds of learning strategies.